2016
DOI: 10.1108/itse-01-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Developing mobile learning practices through teacher education

Abstract: Purpose-This paper reports research that has investigated the context, development and outcomes of a cross-European in-service training programme, seeking to develop mobile learning practices in classrooms. MLEARN, a European Union (EU)-funded project, has explored and promoted teacher development of mobile learning practices in four member states-the Netherlands, the United Kingdom (UK) (England), Greece and Italy. This paper details the ways research findings both fed into and were elicited from this pilot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ever since the Industrial Revolution 4.0, the T&L for TVET system has evolved with the integration of digital elements including Internet of Things, World Wide Web, and virtual classroom. Zozimo (2016) in his study found that teachers and trainers believed the use of technology offered greater flexibility and mobility in the T&L process. He further expressed that it opens the possibility of informality, ownership and inter-weaving learning interactions during the T&L. However, since TVET involves both theory and practical applications, the integration of "learning" and "doing" is compulsory.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ever since the Industrial Revolution 4.0, the T&L for TVET system has evolved with the integration of digital elements including Internet of Things, World Wide Web, and virtual classroom. Zozimo (2016) in his study found that teachers and trainers believed the use of technology offered greater flexibility and mobility in the T&L process. He further expressed that it opens the possibility of informality, ownership and inter-weaving learning interactions during the T&L. However, since TVET involves both theory and practical applications, the integration of "learning" and "doing" is compulsory.…”
Section: Resultsmentioning
confidence: 98%
“…The benefit of these technologies provides flexibility for the teachers in delivering the contents of lessons efficiently. In addition, several other benefits of the technologies include the enhancement of independent learning, customized learning, and reduction in the limitations of time and place of learning (Zozimo, 2016). Contrary to this, the traditional teaching and learning process have been reported to limit active student participation in the classroom.…”
Section: Sustainability Of Tvet Teacher Education Programmementioning
confidence: 99%
“…Gamification that is packaged in the Team Games Tournament (TGT) provided a group role for students so that it stimulates communication and collaboration in solving each challenge. Meanwhile, mobile learning is a flexible container for implementing instructions and challenges from gamification to make learning more meaningful at the level of acting on Edgar Dale's cone of learning experience (Kärki et al, 2018;Passey & Zozimo, 2016). The potential possessed by a combination of mobile learning and gamification can optimize the Sociology learning process by improving students' collaboration skills.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is increased emphasis on the integration of constructivist instructional practices in teaching methods (Dikshit et al, 2013;Passey & Zozimo, 2016;Pinger et al, 2018;Turpen & Finkelstein, 2009). Constructivist instructional practices are the interactive learner-oriented activities of structuring and presenting the learning material in ways that support learners to construct their knowledge of scientific concepts.…”
Section: Integration Of Constructivist Ideas In the Lecture Methodsmentioning
confidence: 99%